2020
DOI: 10.1109/access.2019.2962512
|View full text |Cite
|
Sign up to set email alerts
|

Robust Tracking Control of Aerial Robots Via a Simple Learning Strategy-Based Feedback Linearization

Abstract: To facilitate accurate tracking in unknown/uncertain environments, this paper proposes a simple learning (SL) strategy for feedback linearization control (FLC) of aerial robots subject to uncertainties. The SL strategy minimizes a cost function defined based on the closed-loop error dynamics of the nominal system via the gradient descent technique to find the adaptation rules for feedback controller gains and disturbance estimate in the feedback control law. In addition to the derivation of the SL adaptation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(97 citation statements)
references
References 39 publications
0
93
0
1
Order By: Relevance
“…It is evident from Table 2 that the smoothness of the control input is better in the case of the proposed ANMPC control algorithm as compared to the existing control algorithm. Also, the proposed ANMPC is more energy‐efficient than the FLC 28 and SL‐FLC 45 …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…It is evident from Table 2 that the smoothness of the control input is better in the case of the proposed ANMPC control algorithm as compared to the existing control algorithm. Also, the proposed ANMPC is more energy‐efficient than the FLC 28 and SL‐FLC 45 …”
Section: Resultsmentioning
confidence: 98%
“…Numerically, the tracking performance of the controllers is evaluated by taking integral absolute error (IAE), root mean square error (RMSE), and integral square error (ISE) as the performance index. From Table 2, it is observed that the proposed ANMPC provides low RMSE, IAE, and ISE than the FLC 28 and SL‐FLC 45 . The respective control inputs for both the vertical and horizontal subsystems are presented in Figures 6 and 7 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations